Psychosocial Adaptation to Precocious Puberty: A Nursing Support Program - MİRAL, MUKADDES TURAN; Şahin, Nevin Hotun (Wiley, 2022)
Problem: This study aimed to determine the effects of a nursing support program (NSP) based on the Roy Adaptation Model on the psychosocial adaptation of girls with precocious puberty and their mothers. Methods: This study adopted a pre-post design. It included 26 girls diagnosed with precocious puberty and their mothers. Data were collected using a Demographic Information Form; the Child Behavior Checklist for Ages 6-18; and the Depression, Anxiety, and Stress Scale. Participants were then enrolled in a NSP based on the Roy Adaptation Model. The same measures were administered at the end of the support program to the participants. Findings: It was determined that at the beginning of the program, approximately one-third of the mothers had depression, 15% anxiety, and approximately 20% experienced stress. Mothers' anxiety and stress levels and girls' anxiety/depression and total problem scores significantly decreased after the NSP. Conclusions: The NSP designed for this study positively affected the psychosocial problems of girls with precocious puberty and their mothers.
Keywords: Children; Girls; Mother; Nursing Care; Precocious Puberty; Psychosocial Problems; Roy Adaptation Model